Rasulova, Sabina - (:unkn) unknown (My University, 2026)
Sabina Alimurad Rasulova was born on 17 August 2000. In 2017, she was admitted to Azerbaijan Technical University, Faculty of Transport and Logistics, majoring in Transport Service (Automobile Transport), and completed her bachelor’s degree in 2021. In the same year, she was admitted to the master’s program in Automotive Service Technology at the same faculty and graduated with honors in 2023. In 2023, she was admitted to the doctoral program in Transport Systems Technology and is currently continuing her studies. In 2022, she began her professional career at Azerbaijan Technical University as a Tutor in the Dean’s Office of the Faculty of Transport and Logistics. In 2023, she worked as a Secretary at the same faculty. From 2025 to 2026, she served as a Specialist in the Dean’s Office of the Faculty of Transport and Logistics. Since 2024, she has also been working as an Assistant at the Department of Transport Engineering and Management Technologies.